Peran Guru dalam Implementasi Kurikulum Merdeka untuk Mengembangkan Profil Pelajar Pancasila: (Studi Kasus di Kelas 3 SDN 104203 Bandar Khalipah) - Elfira Veronika; Grecia Gustri Malona; Inggri Lola Amelia; Asiah Ramadhani; Lala Lala; Jelita Ananda; Miftahul Jannah; Tasya Amanda Putri (Jurnal Bintang Pendidikan Indonesia, 2025)
This study aims to analyze the role of teachers in the implementation of the Independent Curriculum to develop the Pancasila Student Profile in grade 3 of SDN 104203 Bandar Khalipah. The main focus of this study is to understand the strategies implemented by teachers, the challenges faced, and the impact of the implementation of the Independent Curriculum on the formation of student character according to the six dimensions of the Pancasila Student Profile. This study uses a qualitative descriptive method with data collection techniques in the form of interviews with grade 3 teachers and distributing questionnaires to students. The results of the study show that teachers act as facilitators in creating an active and innovative learning environment through the implementation of project-based learning and formative assessment. This strategy is effective in building the values of mutual cooperation, independence, and creativity in students. However, teachers face challenges in implementing learning differentiation due to significant differences in student abilities and time constraints in conducting authentic assessments. The conclusion of this study shows that the Independent Curriculum provides flexibility for teachers to adjust learning to student needs, so that they are able to develop characters that are in accordance with the Pancasila Student Profile. Training support for teachers and collaboration with parents are needed to improve the effectiveness of the implementation of the Independent Curriculum in elementary schools.